Readiness of Students in Flexible Learning Modality: A Convergent Parallel Mixed-Methods Study - Rodrigo Jr Licayan; Herrera, Angelli B; Bersano, Michelle S; Idul, Rocris Glenn R (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
This convergent-parallel mixed-methods study was conducted to examine students' readiness on flexible learning modality established in the local context based on Commission on Higher Education Memorandum Order No. 04 series of 2020 or the